التسهيلات الجمركية لتصدير التمور: الأثر والتحديات: Customs facilities for exporting dates: impact and challenges - نضيرة دوبابي; بوطالب براهمي (Journal of North African Economies, 2025)
The date industry in Algeria contributes significantly to both agriculture and the economy, playing a crucial role in meeting human needs, partly ensuring food security, promoting cross-border trade and economic development. The export potential of this industry depends on several factors, including production and marketing capabilities, commitment to quality standards and trade facilitation measures. The current study aims to present the customs facilities linked to the export of Algerian dates, analyze their impact and highlight the issues associated with them. As a result, we hope to enable economic operators to benefit from these facilitation measures, which make it possible to provide a competitive product in global markets.